Analisis Keuntungan dan Efisiensi Produksi Kerupuk Kemplang Ikan pada Skala Rumah Tangga di Kecamatan Kemuning, Sumatera Selatan - Mentari, Rr Dyah Paramitha; Wihardi, Yedi; Harliani, Desliana Opie; Hasibuan, Zhulian Hikmah; Suryati, Ni Komang; S, Rezki Antoni (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
The grilled-kemplang crackers are one of the traditional culinary products of South Sumatra that not only reflect local innovation but also represent the community's adaptation to the availability of raw materials and evolving times. This product plays a significant role in the local economy, particularly as a source of income for household-scale entrepreneurs. This study aims to analyze the profitability and production efficiency of fish-based kemplang crackers at a household scale in Kemuning District. The method used is a survey with purposive sampling techniques, with data obtained through observations, interviews, and literature studies. The survey used a purposive sampling strategy, and information was collected through literature observations, interviews with 30 respondents, and observations. The results of the analysis show that the baked kemplang cracker company has an R/C ratio of 1.93, which shows efficiency and is worthy of development. With total production costs of IDR 318,175.93, the average income per production is IDR 279,018.31. Based on the research results, the baked kemplang cracker business in Kemuning District has proven to be profitable and has a lot of room to develop into a source of income for the residents of Palembang City.